2017
DOI: 10.1007/s10151-017-1657-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of complicated rectovaginal fistulas and the role of omentoplasty

Abstract: Non-resecting methods should be used only in uncomplicated fistulas. Rectovaginal fistulas secondary to inflammatory or malignant disease mostly require extensive therapy. Omentoplasty is effective for the treatment of both high and low rectovaginal fistulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Application of omentoplasty is a well-established option for filling of a presacral cavity after both primary abdominoperineal resection [1] and more complex salvage surgery [25]. Success of an omentoplasty depends on the adequacy of filling the pelvic cavity, determined by the omental volume and length.…”
Section: Introductionmentioning
confidence: 99%
“…Application of omentoplasty is a well-established option for filling of a presacral cavity after both primary abdominoperineal resection [1] and more complex salvage surgery [25]. Success of an omentoplasty depends on the adequacy of filling the pelvic cavity, determined by the omental volume and length.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 16 studies were included in the qualitative synthesis for RVF and AVF: 14 addressing RVF only, 1 addressing AVF only, and 1 addressing both RVF and AVF (combined) (Table 1). Most studies (n = 14) were retrospective cohort studies or case series that met the review de nition for cohort studies [9,14,15,10,[16][17][18][19][20][21][22][23][24][25]. The SLR also included one retrospective, unmatched case-control study [26] and one prospective cohort/registry study [27].…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…'Recurrence rates' were speci cally reported in two studies and ranged from 13.3% (complicated recurrence due to development of multiple perianal stulas with severe sepsis) to 55.8% across multiple procedures [22,24]. Five studies reported post-operative infection rates; however, two [16,22] did not report rates by stula type.…”
Section: Treatment Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Sir, I read with interest the article by E. Schloericke et al [1], entitled "Surgical management of complicated rectovaginal fistulas and the role of omentoplasty" published in Techniques in Coloproctology, in which the authors reported their treatment of rectovaginal fistulas in 58 patients, 19 of whom had a history of cancer with a primary localization in the pelvis. There are important considerations to make before transposing the omentum to the pelvis in patients with cancer.…”
mentioning
confidence: 99%